Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Baju Distro Otsky - Rizky Ramadhan; Defrizal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The problem with this study is that the sales targets for the Otsky distribution fluctuate and are not met each month. Preliminary research showed that only 51% of the 100% sales target was met. Respondents believe that product quality can be imitated by other brands, prices are relatively high compared to competitors, and the lack of promotion for Otsky products causes fluctuations in purchasing decisions. The purpose of this study was to determine the effect of the independent variables, i.e. product quality, price and advertising, on the dependent variables, i.e. Otsky Distro clothing purchase decisions. The study population consisted of his 320 Otsky users, and a sample of 76 respondents was drawn using his Slovin formula. Data were collected using SPSS version 25 statistical software and regression analysis was performed yielding the multiple regression equation Y = 20.128 + 0.388X1 – 0.004X2. The coefficient of determination (R2) is 0.258, indicating that 25.8% of the variability in purchasing decisions can be explained by product quality, price, and advertising. The F-test shows a value of 8.360 at a significance value (Sig) of 0.000. From this we can conclude that product quality, price and advertising have a positive impact on purchasing decisions. The remaining 74.2% are explained by other variables not considered in this study.